LOCAL EXPERIENCE OF TOLVAPTAN IN THE MANAGEMENT OF INPATIENTS WITH SIADH - Sun, Jia Miin; Nasruddin, Azraai Bahari (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Hyponatraemia with sodium (Na) levels of less than 135 mmol/L is the most common electrolyte imbalance in clinical practice. Syndrome of inappropriate antidiuretic hormone secretion (SIADH) is a frequent cause of hyponatraemia, especially in patients with malignancy and can result in prolonged hospitalisation. Tolvaptan, an ADH-receptor antagonist, is a useful option to treat hyponatraemia in patients with SIADH and reduce inpatient stay. We developed a local treatment protocol in 2019 for the use of Tolvaptan in Hospital Putrajaya (HPJ). METHODOLOGY This was retrospective study of inpatient use of tolvaptan in the treatment of SIADH-related hyponatremia in HPJ from January 2020 to March 2023. The criteria for inpatient tolvaptan use were according to the HPJ tolvaptan local guideline. RESULT Data was available for 10 patients. Most of them had malignancy related SIADH. Based on our protocol, all patients were given an initial dose of Tolvaptan 7.5 mg (compared to manufacture recommendation of 15 mg) to avoid the risk of Na overcorrection. The mean baseline Na was 118 mmol/L (range 110-123 mmol/L). The mean rise in Na at 24 hours was 7 mmol/L (range 1-11 mmol/L). 9 patients had Na increment of at least 5 mmol/L at 24 hours. The remaining 1 patient had increment of Na level of only more than 1 mmol/L at 24 hours but responded to Tolvaptan 15 mg subsequently. None of the patients had overcorrection of Na (more than 12 mmol/day over 24 hours) or development of osmotic demyelination syndrome. CONCLUSION This study demonstrated that inpatient tolvaptan use resulted in favourable outcomes. Our local Tolvaptan protocol is safe and effective in the treatment of SIADHrelated hyponatraemia.